Integrasi Zakat dan Pajak dalam Sistem Fiskal di Kota Langsa: Potensi dan Tantangan - Shifah, Layyinatus; Nasution, Yenni Samri Juliati (Universitas Pahlawan Tuanku Tambusai, 2025)
The integration of zakat and taxation within Aceh's fiscal system holds significant potential for increasing regional revenue while enhancing social welfare. This study aims to explore both the potential benefits and challenges of integrating these two instruments. Using a descriptive qualitative approach, data was gathered through literature review, in-depth interviews with relevant stakeholders, and document analysis. Findings reveal that the integration of zakat and taxation has the potential to improve income redistribution and reduce social inequality. However, primary challenges include regulatory disharmony, administrative complexity, and limited public understanding of this integration. To optimize the potential of zakat and tax integration, recommendations include regulatory harmonization between the central and regional governments, administrative strengthening, and public education programs. Effective implementation of this integration could thereby support sustainable development in Aceh.